Microcredit and Women's Empowerment in Rural Bangladesh: Evidence from A Comparative Analysis - Mst. Sathy Aktar; A. K. M. Mahmudul Haque (Inspektorat Kabupaten Majalengka, 2026)
SDGs emphasize gender equality to achieve sustainable and inclusive development. 8FYP of Bangladesh is about to expire, yet most rural women are completely dependent on men socially and economically; microcredit can be a strong instrument to reduce this dependency. This study explores the impacts of microcredit on women's empowerment in rural Bangladesh by comparing microcredit borrower and non-borrower women. A mixed-method study is used with 250 respondents. Among them, 200 respondents (100 borrowers and 100 non-borrowers) participated in a questionnaire survey, while the remaining 50 respondents were interviewed face-to-face. Data were collected using a semi-structured questionnaire following a stratified random sampling technique. The findings reveal that borrower women are significantly ahead in several aspects, such as household decision-making, purchasing essential items, contributing to children’s education expenses, and self-confidence. Statistical analysis highlights an important relationship between microcredit participation and women’s empowerment, with a significant difference between borrowers and non-borrowers (χ² = 63.02, p < 0.001). The study recommends that proper utilization of microcredit, proper training, and monitoring by NGOs can contribute to the advancement of marginalized women.